State-of-Charge Estimation of Li-ion Battery Using Gated Recurrent Unit with One-Cycle Learning Rate Policy - Hannan M.A.; How D.N.T.; Mansor M.B.; Hossain Lipu M.S.; Ker P.; Muttaqi K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Charging (batteries); Deep learning; Digital arithmetic; Electric traction; Ions; Learning systems; Lithium compounds; Lithium-ion batteries; Statistical tests; Comparative evaluations; Feed-forward architectures; Floating point operations per seconds; Generalization capability; Lightweight batteries; Model computation; State-of-charge estimation; Vehicle applications; Battery management systems